2017
DOI: 10.1093/infdis/jix290
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy Targeting Adenosine Synthase A Decreases Severity of Staphylococcus aureus Infection in Mouse Model

Abstract: Staphylococcus aureus is a severe pathogen found in the community and in hospitals. Most notably, methicillin-resistant S. aureus (MRSA) is resistant to almost all antibiotics, which is a growing public health concern. The emergence of drug-resistant strains has prompted the search for alternative treatments such as immunotherapeutic approaches. Previous research showed that S. aureus exploit the immunomodulatory attributes of adenosine to escape host immunity. In this study, we investigated adenosine synthase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…A previous study performed in our laboratory demonstrated that mice vaccinated with recombinant AdsA (rAdsA) induced high titers of anti-AdsA antibodies and provided consistent protection in three mouse infection models under conditions of challenge with S. aureus clinical isolates (19). The remaining two antigens, PmtA and PmtC, belong to Pmt ABC transporter family, an essential S.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study performed in our laboratory demonstrated that mice vaccinated with recombinant AdsA (rAdsA) induced high titers of anti-AdsA antibodies and provided consistent protection in three mouse infection models under conditions of challenge with S. aureus clinical isolates (19). The remaining two antigens, PmtA and PmtC, belong to Pmt ABC transporter family, an essential S.…”
Section: Resultsmentioning
confidence: 99%
“…These have included vaccination with ClfA [12], Als3p [28] and adenosine synthase A [29] in combination with alum and SasX combined with Freund’s adjuvant [30]. These vaccines have had variable efficacy, with only modest protection against SSTIs when ClfA [12] was used as vaccine antigen, supporting the notion that multiple CWA proteins may need to be targeted simultaneously, whereas Als3p [28] and adenosine synthase [29] offered significant protection. In the case of SasX [30], Freund’s adjuvant was used, limiting the potential for translation to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation may contribute to more frequent transmission and spread of the bacteria by causing rashes and skin damage. The finding that the disrupted adsA gene is common in clinical USA500 MRSA isolates from the United States may also be significant in the future given that the encoded surface protein is a potential vaccine target ( 54 ).…”
Section: Discussionmentioning
confidence: 99%